Teaching resources for the improvement of learning in environmental culture - Oblitas De Las Casas, Karla Mariela (2019)
The main objective of this research was to demonstrate that teaching resources in education improve the learning in the environmental culture of the students of the VII cycle of the César Vallejo University of the Chiclayo subsidiary, focusing the theoretical basis on the "Dimensions of Learning" de Marzano (2005), used an instrument of own elaboration and was applied to the students of the Environmental Culture subject of the VII Cycle of the César Vallejo University of Chiclayo. Regarding the research design, it was quasi-experimental and applied type. Through the verification of the results before and after the application of the program, the importance of the use of the didactic resources to improve the learning of the students of the curriculum experience was demonstrated; being that in the present work the "Mind Map" and "The Portfolio" were used as teaching tools.